2011
DOI: 10.1210/en.2011-0263
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sonic Hedgehog-Gli2 Pathway in the Masculinization of External Genitalia

Abstract: During embryogenesis, sexually dimorphic organogenesis is achieved by hormones produced in the gonad. The external genitalia develop from a single primordium, the genital tubercle, and their masculinization processes depend on the androgen signaling. In addition to such hormonal signaling, the involvement of nongonadal and locally produced masculinization factors has been unclear. To elucidate the mechanisms of the sexually dimorphic development of the external genitalia, series of conditional mutant mouse ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 53 publications
5
67
1
2
Order By: Relevance
“…In addition to such early organ size control, several growth factor signals can modulate embryonic masculinization of the size of the GT (3, 7). However, such growth factor-mediated modulation is not sufficient to induce full masculinization of the GT, because gain-offunction mutants for an individual growth factor gene do not exhibit urethral masculinization (3,7). Thus, masculinization of the GT may require definitive tissue differentiation processes as well as its growth regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to such early organ size control, several growth factor signals can modulate embryonic masculinization of the size of the GT (3, 7). However, such growth factor-mediated modulation is not sufficient to induce full masculinization of the GT, because gain-offunction mutants for an individual growth factor gene do not exhibit urethral masculinization (3,7). Thus, masculinization of the GT may require definitive tissue differentiation processes as well as its growth regulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, such genes have not been identified. Recently, growth factor signals have been suggested to regulate the masculinization of the size of GTs (3,7). However, the modulation of such growth factor signals does not induce the urethral masculinization (3, 7).…”
mentioning
confidence: 99%
“…There is literature stating that genotypes that have sonic hedgehog signalling (SHH) problems are likely to present with severe hypospadias and this genotype is also associated with defect on tissue repair and regeneration. [10][11] Our study has the limitation of being a non-concurrent cohort, although no randomization was applied; however, we are able to include all well-defined patients in the set timeframe. Furthermore, the baseline characteristics between groups in this study did not show any statistical significant difference, which supports no involvement of selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Miyagawa et al (2011) have shown that Shh is expressed in the urethral plate epithelium of mice during embryogenesis and that its signal is mediated through Gli2 in the mesenchyme. Gli2 mutants had hypoplasia of the genital tubercle and a cleft at the proximal ventral midline without androgen deficiency.…”
Section: Human Mutationsmentioning
confidence: 99%